Modern Services: Terminological Considerations and the Characteristic Features of Their Role in Socio-Economic Development - Dominiak, Joanna (Quaestiones Geographicae, 2018)
Services, the staple of the modern economy, are subject to constant changes. These changes are contingent on economic processes that are the result of, inter alia, technological progress, intensifying globalisation processes and growing competitiveness. Increasingly important are specialised services, where staff with high qualifications are employed. Such services include dynamically developing knowledge-based ones. Their growth has been fostered by the increasing demand for modern services in the era of the development of a knowledge-based economy. This article focuses on the terminology related to modern services and seeks to answer questions about their role in the development of modern economies. The aim of the article is: (1) to identify modern services in the light of relevant literature; (2) to attempt to construct a model of the impact of those services on economic development; (3) to analyse the level of development of modern services in the EU member states, and (4) to empirically verify the model of the impact of the services on economic development in the EU member states. The empirical analysis was carried out with the application of statistical data from the Eurostat database.